BubR1 Controls Heart Development by Promoting Expression of Cardiogenesis Regulators - Renju Pun; Aradhana Thapa; Sylar R. Takafuji; Rexton M. Suzuki; Gabrielle F. Kay; Toni D. Howard; Michael H. Kim; Brian J. North (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Congenital heart defects are structural anomalies present at birth that can affect the function of the heart. Aneuploidy is a significant risk factor for congenital heart defects. Mosaic variegated aneuploidy syndrome, caused by mutations in Bub1b (encoding BubR1, a mitotic checkpoint protein), leads to congenital heart defects such as septal defects. However, the molecular rationale for how Bub1b mutations promote congenital heart defects associated with mosaic variegated aneuploidy syndrome remains unresolved. Methods To study morphological, structural, and cellular consequences of BubR1 deletion in the heart, we crossed mice carrying conditional alleles of Bub1b with Nkx2.5‐cre mice. Single‐cell RNA sequencing was carried out to determine differentially expressed genes and biological processes in various cell types present in the developing heart. Trajectory analysis was carried out to determine the differentiation trajectory of BubR1 knockout embryonic hearts. Finally, CellChat analysis provided details on the major signaling interactions that were either absent or hyperactive in the BubR1 knockout heart. Results Here, we show that cardiac‐specific BubR1 deletion causes embryonic lethality due to developmental stalling after cardiac looping with defects in cardiac maturation including chamber wall thickness, septation, and trabeculation. Single‐cell transcriptomic profiling further revealed that the differentiation trajectory of cardiomyocytes is severely impacted with suppression of critical cardiogenesis genes. Hyperactivation of Wnt signaling in BubR1 knockout hearts indicated a disturbed homeostasis in cellular pathways essential for proper tissue morphogenesis of the heart. Conclusions Taken together, these findings reveal that BubR1 is a crucial regulator of cardiac development in vivo, which ensures the proper timing of heart morphogenesis.